Bridging In Situ Testing and Constitutive Modelling: An Automated Approach to Soil Parameter Identification - Islam Marzouk; Franz Tschuchnigg (Applied Sciences, 2025)
In situ testing is essential in geotechnical engineering, providing valuable insights into both soil stratification and material behaviour. This paper illustrates an automated framework for deriving constitutive model parameters from in situ test data. The framework employs a graph-based approach that enhances both transparency and adaptability—transparency by explicitly tracing the computation of each parameter and adaptability by allowing users to incorporate their expertise. The study applies this framework to a marine clay test site, demonstrating its ability to determine soil parameters efficiently. Additionally, the framework is directly integrated into a finite element software, enabling seamless parameter transfer for numerical modelling. A case study is presented in which a shallow foundation is simulated to illustrate the practical application of this approach. This framework is particularly valuable in the early stages of geotechnical projects, providing detailed soil characterisation when site data is limited. Validating the accuracy of the derived parameters and incorporating additional in situ test methods are part of ongoing research.